Requirements for Using e-learning in the physical learning environment at Higher Education from the Point of View of Educational Specialists - Al-Awad, Rehab Bashir Hassan; El-Sadek, Hatem Abdel Maged (Journal of Educational and Psychological Sciences, 2019)
The study aimed to identify the necessary requirements needed for employing eLearning in the physical learning environment from the point of view of the teaching staff. In this study the researcher employed the analytical descriptive method and the size of the sample in which the study was applied was (127) individuals from the teaching staff with a degree of a teaching assistant and above, The researcher has employed questionnaire technique as a study tool, and the most important findings of the study are: The study has come to the fact that the majority of the researchers managed to answer the study areas which are summarized in the requirements needed for employing e. learning by the educational environment which was specified by this study، these requirements are vitally important from the point of view of the teaching staff. And the most important recommendations of the study are: Providing all the requirements needed to put e. learning into practice in the physical educational environment which was determine by the study to employ eLearning in the institutions of the higher education in Sudan.